ANCA associated pauci-immune retinal vasculitis. Issue 5 (15th April 2005) - Gallagher, M J; Ooi, K G-J; Thomas, M; Gavin, M
Abstract : Background: Antinuclear cytoplasmic antibodies (ANCA) are useful diagnostic serological markers for the most common forms of necrotising vasculitis. ANCA associated vasculitides represent distinctive clinicopathological categories—for example, Wegener's granulomatosis, Churg-Strauss syndrome, microscopic polyangiitis, and idiopathic necrotising crescentic glomerulonephritis, collectively known as the small vessel pauci-immune vasculitides. Method: Three cases of ANCA associated pauci-immune retinal vasculitis are described. Their systemic features are described and the clinical significance of ANCA as a diagnostic test in relation to retinal vasculitis discussed. Results: These three cases represent a spectrum of clinical features associated with retinal vasculitis. Two cases have evolved into clinical recognisable entities as microscopic polyangiitis. Adherence to the international consensus statement on testing and reporting of ANCA is recommended and the authors speculate that the incidence of microscopic polyangiitis may be underestimated because of the under-recognition of systemic involvement in patients with retinal vasculitis. Conclusion: The receipt of a positive ANCA result should always raise the suspicion of a pauci-immune systemic vasculitis and prompt appropriate investigation. The authors emphasise the importance of the evaluation of systemic features in these patients with retinal vasculitis, enabling earlier recognition and thereby preventing significant morbidity and mortality.